2022
DOI: 10.1038/s41598-022-23479-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of antibiotic resistance genotypes of Vibrio species recovered from selected freshwaters in Southwest Nigeria

Abstract: Vibrio species are classified as potent hazards because of their tendency to effect serious diseases like cholera and other gastrointestinal ailments in humans, as well as vibriosis in fish. A total of 144 freshwater samples were aseptically collected monthly across four rivers (Asejire, Ona, Dandaru and Erinle rivers) over a 12-month period from which Vibrio spp. were isolated using culture procedures, confirmed by means of biochemical test as well as Polymerase Chain Reaction (PCR) assay and further characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 72 publications
0
5
1
Order By: Relevance
“…Similarly, a strong relationship between the tetracycline resistance phenotypes of V. parahaemolyticus isolates and the presence of ARG was also determined, as tetA was detected in 23 of 27 isolates that exhibited resistance to tetracycline. The overall level was found to be much higher than reported in other studies [ 45 , 51 ] in which the detection rate of tetA was 28% to 30% of tetracycline-resistant isolates. Meanwhile, tetA was undetected in all V. parahaemolyticus strains that exhibited resistance to tetracycline [ 5 , 52 ].…”
Section: Discussioncontrasting
confidence: 74%
“…Similarly, a strong relationship between the tetracycline resistance phenotypes of V. parahaemolyticus isolates and the presence of ARG was also determined, as tetA was detected in 23 of 27 isolates that exhibited resistance to tetracycline. The overall level was found to be much higher than reported in other studies [ 45 , 51 ] in which the detection rate of tetA was 28% to 30% of tetracycline-resistant isolates. Meanwhile, tetA was undetected in all V. parahaemolyticus strains that exhibited resistance to tetracycline [ 5 , 52 ].…”
Section: Discussioncontrasting
confidence: 74%
“…Unlike the 31.2% MDR rate observed in this study, some other studies had recently reported 100% MDR rates in Vibrio isolates (Gxalo et al, 2021;Omoruyi & Ojubiaja 2022). These studies also differed from this (Odjadjare & Igbinosa, 2017;Adesiyan et al, 2022;Oko et al, 2022).…”
Section: Discussionmentioning
confidence: 75%
“…Other studies simply tested against ampicillin and reported rates ranging from 76.92% to 94.1% (Islam et al, 2021;Gxalo et al, 2021). A 2022 study however had a much lower rate of amoxicillin resistance (45%) reported (Adesiyan et al, 2022). Low rates of resistance were noted against gentamicin, ofloxacin and ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“… 45/300 (15) bla NDM-1 NA [ 121 ] NA Vegetables, borehole and well water E. coli 8/100 (8) NA NA [ 122 ] NA Freshwater from river Vibrio spp. 28/315 (8.9) NA NA [ 123 ] NA Fish and Fish Storage Water Vibrio spp. 113/128 (88.3) NA NA [ 124 ] NA Rectal swab samples of poultry, beef, cattle, poultry and beef vendor table E. coli 78/138 (56.5) NA NA [ 125 ] Reunion island 2016–2017 Pig E. coli, K. pneumoniae 2/181 (1.1)* NA NA [ 126 ] Senegal 2010–2011 Human head lice A. baumannii 3** bla OXA23 -like NA [ 127 ] 2016 Fecal samples of Wild Chimpanzees, Termites K. pneumoniae 23** bla OXA-48 , bla KPC-2 ...…”
Section: Resultsmentioning
confidence: 99%